Genetic analysis and identification of low‐resistivity gas reservoirs of southwestern Sulige gas field in China. Issue 8 (9th June 2022) - Yang, Zhen; Zhang, Xiaoli; Lu, Junhui; Li, Yajun
Abstract: Sulige gas field is the largest natural gas producing area in China. Due to the "water blocking" effect, the gas–water layer significantly influences the development of gas reservoirs. The existence of low‐resistivity gas layers in the He 8 member of the Shihezi Formation in the southwestern Sulige gas field makes it challenging to distinguish the gas layers from the gas–water layers using conventional identification methods. To effectively identify the low‐resistivity gas layers, their genetic mechanisms are analyzed by studying their lithology and pore structural characteristics based on the well logging and core experimental data. The low‐resistivity gas layers are main affected by three causes: (1) electrical conductivity of argillaceous laminae in sandstone, (2) additional conductivity of clay minerals, and (3) high bound water saturation caused by the development of micropores and clay minerals in sandstone. Herein, to effectively distinguish the low‐resistivity gas layer from the gas–water layer based on the genetic mechanism of the low‐resistivity gas layer, first, a gas‐bearing index was constructed to characterize the gas‐bearing properties of the reservoir using the neutron logging and density logging curves after eliminating the influence of the dispersed shale. Second, a model to calculate the bound water saturation was constructed by selecting sensitive parameters with respect to the causes of bound water. Then, two plots, namely the gas‐bearing index–natural gamma relative value cross‐plot and the bound water content–porosity cross‐plots, were constructed using the gas testing data, and the identification standard of the low‐resistivity gas and gas–water layers was established. The interactive identification of the two cross‐plots effectively distinguished the low‐resistivity gas layer from the gas‐water layer, thereby providing a basis for understanding the distribution of gas and water in the southwestern Sulige gas field, which may guide further exploration and the deployment of the development well pattern. Abstract : Argillaceous lamina, clay minerals, and the development of micropores are the main causes of low resistivity. Capillary bound water and in‐wall bound water coexist and both contribute to the low resistivity. The influence of clay on neutron logging was corrected by Pe logging data.